Implementasi Peraturan Daerah Kota Pariaman Nomor 6 Tahun 2013 Tentang PBB Perdesaan Dan Perkotaan di Kelurahan Jawi-Jawi II - Herza Netti; Syamsir Syamsir; Aldri Frinaldi; Vika Yyanka; Muhammad Hafiz (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The transfer of power from the center to the regions is a challenge that must be overcome by cities/districts throughout Indonesia with the implementation of governance and development using the APBD. One way to increase the APBD is by collecting taxpayers. Perda Pariaman No 6,2013, Pariaman implements the Collection of Rural and Urban Land and Building Taxes.On Indonesia's 76th Independence Day, 21 Villages/Kelurahan in Kota Pariaman received awards for paying PBB-P2. The PBB-P2 collection in the Jawi-Jawi II Village, Pariaman City, has a low level of achievement of the PBB-P2 target. Qualitative research methods by collecting data through interviews and field observations are expected to explain the implementation of Perda Pariaman No 6, 2013 in the Jawi-Jawi II sub-district and to identify obstacles to implementing this policy. The application of the policies studied based on Edward III's theory, namely communication, resources, disposition and bureaucratic structure, has not achieved the expected results. This is due to a shortage of tax collection officers as wellthe lack of awareness of the people of the Jawi-Jawi II kelurahan about the importance of paying land and building taxes. Taxpayers do not fully fulfill their obligations as taxpayers and not all taxpayers know the procedures and rules that apply to the issuance of SPPT, so that the administrative process does not run as expected, because there are still external restrictions that lead to the loss of potential PBB taxes.